The Effect of Company Growth, Current Ratio and Leverage Ratio of Dividend Policy in Trade, Services, and Companies Investment That is on The IDX - Holfian Daulat Tambun Saribu; Januardin Januardin (Syntax Corporation Indonesia, 2021)
The purpose of this study was to determine the effect of Company Growth, Current Ratio and Leverage Ratio on Dividend Policy in Trade, Services and Investment Companies in the Indonesia Stock Exchange in 2014-2018. The independent variables used in this study are, Company Growth, Current Ratio and Debt Equity Ratio while the dependent variable is dividend policy. The sampling method used was purposive sampling technique. The number of samples obtained was 15 companies. The data used in this research is secondary data. Analysis techniques The analysis model uses multiple linear regression equations. The results show that partially the leverage ratio has a negative effect on dividend policy. The results of this study indicate simultaneously, Company Growth, Current Ratio and Debt Equity Ratio significantly influence dividend policy with a significance level of 0,000. Adjusted Square value shows the results of 12.7% of the dividend policy influenced while the remaining 87.3% is influenced by other variables outside this study.